The effect of interface angle on the thermal conductivity of Si/Ge superlattices. Issue 40 (8th October 2021) - Liu, Ying-Guang; Ren, Guo-Liang; Chernatynskiy, Aleksandr; Zhao, Xiao-Feng
Abstract : The special interface angle arrangement induces coherent transport of phonons and significantly improves the thermal conductivity. Abstract : Si/Ge superlattices (SLs) are good candidates for thermoelectric materials because of their remarkable thermal insulating performance compared with their bulk counterparts. In this paper, the non-equilibrium molecular dynamics (NEMD) simulation method was applied to investigate the thermal conductivity of Si/Ge SLs containing tilted interfaces. It was found that the thermal conductivity will be 4–5 times higher than that of other angles when the period length is 4–8 atomic layers and the interface angle is 45°. This phenomenon can be attributed to the smooth arrangement of the 45° interface which induces phonon coherent transport. Meanwhile, the thermal conductivity has not been improved due to the phonon localization although the phonons satisfy the coherent transport when the interface angle is 90°. Interestingly, the thermal conductivity is almost unchanged with the increasing interface angle when the period length is large enough which exceeds 20 atomic layers. The main reason for the unchanged thermal conductivity is due to the period length which is greater than the phonon coherence length inducing the phonon incoherent transport.